2020
DOI: 10.1016/j.ejpb.2020.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes as tunable platform to decipher the antitumor immune response triggered by TLR and NLR agonists

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Liposome Formulation: Multilamellar vesicles (MLV) were prepared by using a lipid film hydration technique as described previously by Jacoberger et al [58] Briefly, a chloroform/methanol solution (9/1 v/v) containing a mixture of lipids and light-sensitive molecules, were mixed in a round-bottom Pyrex tube, and was completely dried under high vacuum for 45 min. The resulting lipid film was then hydrated in 10 × 10 −3 m HEPES, 150 × 10 −3 m NaCl, pH 7.1 containing 10 × 10 −3 m ascorbic acid at a final phospholipid concentration of 10 × 10 −3 m, leading to the formation of MLV.…”
Section: Methodsmentioning
confidence: 99%
“…Liposome Formulation: Multilamellar vesicles (MLV) were prepared by using a lipid film hydration technique as described previously by Jacoberger et al [58] Briefly, a chloroform/methanol solution (9/1 v/v) containing a mixture of lipids and light-sensitive molecules, were mixed in a round-bottom Pyrex tube, and was completely dried under high vacuum for 45 min. The resulting lipid film was then hydrated in 10 × 10 −3 m HEPES, 150 × 10 −3 m NaCl, pH 7.1 containing 10 × 10 −3 m ascorbic acid at a final phospholipid concentration of 10 × 10 −3 m, leading to the formation of MLV.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that dsRNA targeting RLRs could be encapsulated into lipid-based NPs and polymeric NPs for systemic delivery in murine pancreatic cancer and breast cancer models ( 102 , 103 ). In a study comparing the antitumor immunity carried out by liposomal TLR agonists and NLR agonists, NLR agonists also exhibit early antitumor activity ( 104 ). However, the antitumor activity of NOD1 agonist was not associated with DC-driven adaptive immune responses, suggesting that NOD1 activation would trigger an alternative cytotoxic adaptive immune response against tumor which differs from TLR agonists.…”
Section: Small Molecule-based Immune Activationmentioning
confidence: 99%
“…For instance, Jacoberger-Foissac et al designed a liposome platform consisting of an MHC class I epitope peptide from human papillomavirus (HPV) 17 E7, MHC class II epitope peptide, which is universal and derived from influenza virus, and an immune agonist. This could induce potent Th1-oriented antitumor immunity and the migration of skin DCs to draining lymph nodes [76,168]. Another example of combination therapy is to combine TSAs and specific mAbs targeting APCs.…”
Section: Cooperative Combat Against Cancermentioning
confidence: 99%